Uncommon Alliances : Cultural Narratives of Migration in the New Europe - Kovačević, Nataša, 1973- (Edinburgh University Press, 2018)
Examines European Union's neocolonial sovereignty in cultural narratives of migration. 'Uncommon Alliances' takes a critical stance toward both assimilationist and multicultural imaginings of community in the European Union that occlude neocolonial relations of dependence and exclusion. Brining into conversation postcolonial and post-communist migration narratives from Africa, Asia and Eastern Europe, it aims to capture the emergent shift from national to postnational European space. Through its examination of cultural texts, including works by Jamal Mahjoub, Mike Phillips, Laila Lalami, Mahi Binebine, Dubravka Ugrešić and others, this book traces European Union neocolonial practices in relation to European history, borders and guiding ideals of community, which exclude various 'others' from their symbolic imaginary. The book deliberately moves the discussion away from social-scientific approaches to humanities and offers a fresh intellectual framework for understanding multicultural identity in Europe. Goes beyond traditional frameworks of cultural analysis (national, ethnic, or language-based) by focusing on narratives which take the European Union as a point of reference. Shifts focus from narratives depicting interactions between different cultures to those imagining communities of solidarity based on common economic or historical marginalisation in the European Union. Revises postcolonial theory by arguing that the European Union exemplifies a new, 'consensual' regime of colonial governance.